2021
DOI: 10.1245/s10434-021-09904-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Genomics to the Surgical Management and Study of Oral Cancer

Abstract: Background Oral squamous cell carcinoma (OSCC) is the most frequent type of tumor arising from the oral cavity. Surgery is the cornerstone of the treatment of these cancers. Tumor biology has long been overlooked as an important contributor to the outcome of surgical procedures, but recent studies are challenging this concept. Molecular analyses of tumor DNA or RNA provide a rich source of information about the biology of OSCC. Methods We searched for rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 115 publications
(218 reference statements)
0
8
0
5
Order By: Relevance
“…Moreover, in a previous NMR spectroscopy study [33], specific variations in the salivary metabolomic profile were identified and revealed that fucose, glycine, methanol, and proline were highly discriminant between patients with HN cancer and control subjects. Further, metabolomics studies revealed high sensitivity to saliva metabolic changes [34] and to DNA methylation alterations (that are detectable in saliva) of patients with oral squamous cell carcinoma (OSCC) [35][36][37], suggesting that salivary biomarkers are valuable for OSCC early diagnosis and OSCC stratification. Altogether, these elements emphasize the importance of conducting further metabolomics studies with concomitant in-vivo and ex-vivo biofluids (serum and/or saliva) 1 H-MRS analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a previous NMR spectroscopy study [33], specific variations in the salivary metabolomic profile were identified and revealed that fucose, glycine, methanol, and proline were highly discriminant between patients with HN cancer and control subjects. Further, metabolomics studies revealed high sensitivity to saliva metabolic changes [34] and to DNA methylation alterations (that are detectable in saliva) of patients with oral squamous cell carcinoma (OSCC) [35][36][37], suggesting that salivary biomarkers are valuable for OSCC early diagnosis and OSCC stratification. Altogether, these elements emphasize the importance of conducting further metabolomics studies with concomitant in-vivo and ex-vivo biofluids (serum and/or saliva) 1 H-MRS analyses.…”
Section: Discussionmentioning
confidence: 99%
“…La mise au point d'un diagnostic biologique objectif de malignité serait donc un avantage majeur pour cibler les patients candidats à une exérèse. Différentes stratégies peuvent être appliquées selon le type d'anomalie détectée : mutations ou altérations du nombre de copies de gènes, profils transcriptomiques, ou marques épigénétiques [7]. Une analyse transcriptomique pourrait, par exemple, aider à caractériser l'infiltrat inflammatoire, spécifique lors du développement malin de la tumeur [12].…”
Section: Analyser La Biologie Tumorale Pour Aider à Définir Certaines...unclassified
“…L'émergence d'atlas comme le TCGA (The Cancer Genome Atlas) permet aujourd'hui un accès libre aux données de génomique et de protéomique, et donc d'envisager une nouvelle taxonomie moléculaire des tumeurs [4,5]. Grâce aux développements des techniques fondées sur l'analyse des acides nucléiques libérés par les cellules tumorales, il devient également envisageable de « sonder » de façon non invasive, par biopsies liquides, le génome tumoral, en particulier en amont de la procédure chirurgicale [6,7]. La montée en puissance des traitements ciblés a par ailleurs constitué une avancée conceptuelle majeure.…”
unclassified
See 1 more Smart Citation
“…Relevant studies have confirmed that pathogenic bacteria can easily colonize and multiply in the oral cavity of the organism, and normal people can effectively remove oral pathogenic bacteria due to their own cleansing function, which makes the incidence of serious infection low [ 18 , 19 ]. However, postoperative oral cancer patients have surgical trauma in the oral cavity, and the daily secretion of blood and saliva is significantly reduced.…”
Section: Introductionmentioning
confidence: 99%